An update on the pathogenic role of IL-6 in rheumatic diseases. (October 2021) - Kaneko, Yuko; Takeuchi, Tsutomu
Highlights: IL-6 is one of key cytokines in the pathogenesis of various rheumatic diseases. Direct inhibition of the IL-6 pathway is highly effective in some rheumatic diseases. IL-6 may not be a main driver in some diseases where IL-6 inhibition is not effective. IL-6 inhibition for severe COVID-19 shows mixed results depending on protocols. Abstract: Interleukin (IL)-6 is a pleiotropic cytokine that is involved in the pathogenesis of various rheumatic diseases. Direct inhibition of the IL-6 pathway by an anti-IL-6 receptor or inhibiting the ligand itself has proved to be efficacious in the treatment of these diseases. Juvenile idiopathic arthritis, adult-onset Still's disease, large vessel vasculitis including giant cell arteritis and Takayasu disease, systemic sclerosis, and polymyalgia rheumatica respond well to IL-6 inhibition as expected. However, no clinically meaningful effect has been observed with regard to IL-6 blockade in ankylosing spondylitis, psoriatic arthritis, and systemic lupus erythematosus. This review discusses the current state of IL-6 targeting approaches in various rheumatic diseases other than rheumatoid arthritis.